2014
DOI: 10.1002/2013jd020592
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of impact of domain size and parameterization scheme on simulation of tropical cyclones in the Bay of Bengal

Abstract: [1] A large number of processes and factors control the quality of simulations with a numerical weather prediction model and especially with mesoscale models; identification and optimization of these processes are critical for improving forecast skill. The importance of cumulus parameterization schemes in simulation of tropical cyclones was recognized early, and a large number of studies have addressed this issue. However, certain other aspects have received relatively less attention. In particular, unlike sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Wang et al [9] examined the sensitivity of heavy precipitation to horizontal resolution, domain size, and rain rate assimilation for case studies using a convection-permitting model. Dravitzki and McGregor [10] investigated heavy rainfall events over the Waikato River Basin of New Zealand generated with higher-resolution WRF, and Goswami et al [11,12] showed that domain size is as important as grid spacing and initial conditions for heavy rainfall events. Additionally, Li et al [13] analyzed the influence of horizontal resolution, domain size, and physical parameterization schemes to evaluate an optimized WRF precipitation forecast over a region of complex topography during the flood season.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [9] examined the sensitivity of heavy precipitation to horizontal resolution, domain size, and rain rate assimilation for case studies using a convection-permitting model. Dravitzki and McGregor [10] investigated heavy rainfall events over the Waikato River Basin of New Zealand generated with higher-resolution WRF, and Goswami et al [11,12] showed that domain size is as important as grid spacing and initial conditions for heavy rainfall events. Additionally, Li et al [13] analyzed the influence of horizontal resolution, domain size, and physical parameterization schemes to evaluate an optimized WRF precipitation forecast over a region of complex topography during the flood season.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the mesoscale forecasts of temperature, relative humidity and wind speed at the 2 m level with the COMoN profiler (NPL) shows (Figure ) the daily forecasts (2 m level) to be significantly correlated (95% confidence) with the corresponding observations for most cases except for some of the months. Several earlier studies (Goswami et al ., , ; Goswami and Mallick, ; Goswami and Mohapatra, ) have also shown the applicability of the WRF model over India. It may be seen, however, that the simulated daily maximum often occurs earlier by 1 or 2 h than the observation.…”
Section: Resultsmentioning
confidence: 97%
“…This implies that the 12 km model (ERAI_12 and Had2_12) tends to simulate a less favourable environment for TC development as compared with the 25 km model (ERAI_25 and Had2_25). In general, the simulated TC‐associated environments can help to explain the under‐predicted frequency of very intense TCs in the 12 km model, although the simulation of TC intensity also depends on multiple factors such as the model dynamical core (Reed et al, ), the size of domain (Landman et al, ; Goswami and Mohapatra, ) and convection parametrization (Knutson and Tuleya, ), etc.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, with limited computational resources, it is computationally prohibitive to use large ensembles at the spatial resolutions sufficient to simulate TC properties close to reality and it is difficult to robustly quantify model uncertainty in simulating TCs when only a limited number of ensemble members are possible. Hence, it is still important to use single‐model experiments to better understand the physics of model biases and the response of simulated TCs to different model configurations, including the effect of the spatial resolution (Davis et al, ), dynamical core (Reed et al, ), lateral boundary scheme (Wang et al, ), physical parametrizations (Kepert, ; Green and Zhang, ; Jin et al, ; Lim et al, ), the size of domain (Landman et al, ; Goswami and Mohapatra, ) and spectral nudging (Choi and Lee, ). To make sure that TCs are simulated realistically in RCMs, the resolution and the choice of domain needs to be carefully selected.…”
Section: Introductionmentioning
confidence: 99%